Investigating EFL lecturers’ perceived and demonstrated TPACK competence in online and blended language teaching - Arriyani, Nurfisi; Hartono, Rudi; Fitriati, Sri Wuli; Pratama, Hendi (Journal on English as a Foreign Language, 2025)
In response to the shift to online instruction, English language lecturers in Indonesian higher education are expected to integrate digital tools that embody technological, pedagogical, and content knowledge (TPACK). Prior studies often report only tool use frequency, neglecting whether such use advances language teaching goals. This study investigates Indonesian EFL lecturers’ perceived and demonstrated TPACK competence through their use of digital tools and instructional strategies in online English teaching. This convergent mixed-method study examined 59 EFL lecturers from universities across Java, Sumatera, and Sulawesi. Data were garnered from closed and open-ended questionnaires using digital tools. Quantitative analysis using SPSS showed relatively high perceived TPACK competence, with a mean score of 3.962 (SD = 0.826) on a five-point Likert scale measuring tool selection aligned with TPACK principles. Frequently used tools included WhatsApp and the campus Learning System, while Flipgrid and Google Docs were popular for speaking and writing. Thematic analysis revealed varying TPACK alignment; some lecturers deliberately integrated tools for pedagogy and content, whereas others selected technologies mainly for convenience or institutional constraints. Findings suggest that, despite widespread technology use, stronger pedagogical support and ongoing TPACK-focused professional development are essential for meaningful integration in Indonesia.